Making an impact on policing and crime: psychological research, policy and practice - Stott, Clifford John T.; Bradford, Ben (Routledge psychological impacts, 2021)
"Making an Impact on Policing and Crime: Psychological Research, Policy, and Practice applies a range of case studies and examples of psychological research by international, leading researchers to tackle real-world issues within the field of crime and policing. Making an Impact on Policing and Crime documents the application of cutting-edge research to real-world policing and explains how psychologists' insights have been adapted and developed to offer effective solutions across the criminal justice system. The experts featured in this collection cover a range of psychological topics surrounding the field, including the prevention and reduction of sexual offending and reoffending, the use of CCTV and 'super-recognisers,' forensic questioning of vulnerable witnesses, the accuracy of nonverbal and verbal lie detection interview techniques, psychological 'drivers' of political violence, theoretical models of police-community relations, and the social and political significance of urban 'riots.' This collection is a vital resource for practitioners in policing fields and the court system and professionals working with offenders, as well as students and researchers in related disciplines"--